Words most often misspelled and mispronounced - Gallagher, Ruth Gleeson; Calvin, James (New York : Pocket Books, 1963)
A basic refrence guide to the 23,000 trickiest words in the English language. Specially designed to provide quick answers to the correct spelling and pronounciation of the words most likely to be looked up by office workers, speakers, writers and students.
Keywords: English language -- Pronunciation; Spellers